2012
DOI: 10.1111/j.1540-6210.2012.02678.x
|View full text |Cite
|
Sign up to set email alerts
|

Designing Public Participation Processes

Abstract: The purpose of this Theory to Practice article is to present a systematic, cross‐disciplinary, and accessible synthesis of relevant research and to offer explicit evidence‐based design guidelines to help practitioners design better participation processes. From the research literature, the authors glean suggestions for iteratively creating, managing, and evaluating public participation activities. The article takes an evidence‐based and design science approach, suggesting that effective public participation pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
325
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 423 publications
(368 citation statements)
references
References 100 publications
(121 reference statements)
7
325
0
7
Order By: Relevance
“…Future research could also systematically integrate the role of various boundary conditions for governance strategies. Cases in point are numerous rules for designing effective participatory processes and deliberation [28,70].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future research could also systematically integrate the role of various boundary conditions for governance strategies. Cases in point are numerous rules for designing effective participatory processes and deliberation [28,70].…”
Section: Discussionmentioning
confidence: 99%
“…In the field of environmental management, participatory approaches apparently do not necessarily benefit complex problem solving [26,27]. Research suggests that the relevance of specific participatory approaches to address problems is dependent on particular goals and context factors [28], such as the degree of informational and normative uncertainty [29]. Moreover, it has been suggested that further governance dimensions such as precise rules can impact the achievement of environmental management goals [30].…”
Section: Introductionmentioning
confidence: 99%
“…Cabe apuntar que respecto a la participación se ha dividido cada ítem relacionado con la participación en dos en base a Young (1991), que toma en consideración la participación tanto de los ciudadanos como los representantes de éstos en los procesos de planificación y prestación de los servicios para que una Administración Pública esté orientada. Pero también teniendo en cuenta diversos trabajos sobre la participación ciudadana o participación pública (Thomas, 1995(Thomas, y 2012Irvin y Stansbury, 2004y Bryson et al, 2013 que hacen referencia no solo a los ciudadanos sino también a los stakeholders. En consecuencia, se han incorpora los ítmes C8, C10 y C12.…”
Section: Tabla 11 Escala De Orientación Al Servicio Del Públicounclassified
“…Although government administrators, officials, and community leaders have long recognized the value of public participation for a variety of purposes, processes, and decisions (Bryson et al, 2013;Yang & Pandey, 2011) and it is undoubted that local community involvement in the decision making process will enhance the outcome of the framework of a proposed development plan, they frequently do not have a good understanding of how to design participation processes to achieve desirable outcomes. Therefore this paper highlights the difficulties in implementing public participation strategy given that the existing public administration systems as well as legal structure are practiced at inappropriate standards.…”
Section: S O C I O L O G I J a I P R O S T O Rmentioning
confidence: 99%